Maximum value

Calculus Level 4

If x , y x,y are real numbers where x + y = 1 x+y = 1 , determine the maximum value of ( x 3 + 1 ) ( y 3 + 1 ) (x^3+1)(y^3+1) .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Here X+Y=1 so X^3+Y^3 +3XY(X+Y)= 1 => X^3+Y^3+3XY=1 [ given, X+Y=1] => X^3+Y^3= 1-3XY and so alpha= (X^3+1) (Y^3+1)= X^3+Y^3+X^3 Y^3+1 = X^3 Y^3+1+1-3XY = X^3 Y^3-3XY+2 now let XY=D so we can write alpha = D^3-3D+2 and now differentiate alpha with respect to D. and we get 3D^2-3 which must be equal to 0 for getting the maximum value of the above expression. and then D=XY= +/- 1 and given X+Y=1 and we get X-Y = square root 5 by putting value of XY =-1 cause if we putting XY=+1, X-Y will become an imaginary number which is invalid. Then we get the value of X and Y as (1+Sq. root 5)/2 and (1-sq. root 5)/2 respectively. and by putting these values we get the maximum value of alpha =4 Answer: 4

We can graph ( x 3 + 1 ) { ( 1 x ) 3 + 1 } \ \ (x^3+1)\{\ (1-x)^3+1\} and get the maximum.

Niranjan Khanderia - 5 years, 8 months ago

Log in to reply

Hm, that's not a very easy graph to know how to draw. Ultimately, to find the maximum, you will need to differentiate to find the value.

Calvin Lin Staff - 5 years, 8 months ago

Log in to reply

I do not know of other calculators but in even old TI-83 Plus, it is very easy to draw and the graph very clearly shows the two maxima as for 4. We can use zoom box for more accuracy. We use ( x 3 + 1 ) { ( 1 x ) 3 + 1 } (x^3+1)\{(1-x)^3+1\} to plot the graph of one variable.

Niranjan Khanderia - 5 years, 8 months ago

did the same way

Samarth Agarwal - 5 years, 8 months ago

Or you can use Lagrange Multipliers.

Kartik Sharma - 5 years, 8 months ago
Mosaab Mattar
Oct 19, 2015

Start by writing y in terms of x

( ( 1 x ) 3 + 1 ) ( x 3 + 1 ) ( (1 - x)^{3} + 1)( x^{3} + 1)

Expand and differentiate it with respect to x

d d x ( x 6 + 3 x 5 3 x 4 + x 3 + 3 x 2 3 x + 2 ) \frac{d}{dx} (-x^{6} + 3 x^{5} - 3 x^{4} + x^{3} + 3 x^{2} - 3 x + 2)

Find the roots of the resultant derivative; this is done by equating it to zero and solving for x

6 x 5 + 15 x 4 12 x 3 + 3 x 2 + 6 x 3 = 0 - 6 x^{5}+15 x^{4} - 12 x^{3} + 3 x^{2} + 6 x - 3 = 0

Once this is done you will have 3 real roots (and 2 imaginary/complex roots which we will neglect) The real roots would be the following: 1 2 \frac{1}{2} , 1 2 5 2 , 1 2 + 5 2 \frac{1}{2} - \frac{\sqrt{5}}{2}, \frac{1}{2} + \frac{\sqrt{5}}{2} )

Finally plug any of the real roots , with an exception to 1 2 \frac{1}{2} , back into the original function and you would get the maximum value

E.g. ( ( 1 1 2 + 5 2 ) 3 + 1 ) ( ( 1 2 5 2 ) 3 + 1 ) = 4 ((1 - \frac{1}{2} + \frac{\sqrt{5}}{2})^{3} + 1)( (\frac{1}{2} - \frac{\sqrt{5}}{2})^{3} + 1) = \boxed{4}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...